2015
DOI: 10.1016/j.ijmecsci.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Influences of residual stresses and initial distortion on springback prediction of 7B04-T651 aluminium plates in creep-age forming

Abstract: Abstract. Springback behaviour of surface-machined 7B04-T651 aluminium plates of 3 to 8 mm thicknesses, creep-age formed under a single curvature bending radius of 1200 mm, has been experimentally investigated. The surface residual stress levels of the plates have been measured and the typical residual stress distribution and values in 7000-series aluminium alloys have been reviewed and analysed. Finite element models have been developed to simulate creep-age forming (CAF) processes and predict the amount of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 32 publications
(33 reference statements)
0
16
0
Order By: Relevance
“…Based on the FE-simulated results which show a 0.4% difference between the two plates, it can be concluded that the springback sensitivity to a 0.1 mm difference in plate thickness is close to negligible under the current CAF condition. Therefore, the 4.2% difference between the experimental springback values of the two plates is likely to be due to experimental uncertainties, which may include their difference in residual stress level and initial plate distortion prior to CAF submission [6]. Nonetheless, the measured and FE-simulated results both show a decrease in springback as the plate thickness increases from 8.1 to 8.2 mm.…”
Section: Yield Strength Predictionmentioning
confidence: 98%
See 2 more Smart Citations
“…Based on the FE-simulated results which show a 0.4% difference between the two plates, it can be concluded that the springback sensitivity to a 0.1 mm difference in plate thickness is close to negligible under the current CAF condition. Therefore, the 4.2% difference between the experimental springback values of the two plates is likely to be due to experimental uncertainties, which may include their difference in residual stress level and initial plate distortion prior to CAF submission [6]. Nonetheless, the measured and FE-simulated results both show a decrease in springback as the plate thickness increases from 8.1 to 8.2 mm.…”
Section: Yield Strength Predictionmentioning
confidence: 98%
“…Flexible forming surfaces were on both sides of the plate with an additional elastomeric sheet layer between the plate and lower flexible surface. Further details about the method of CAF tool design and test setup can be found in [5] and [6] respectively. The main steps of the forming test include:…”
Section: Creep-age Forming Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the difference between FE and experimental results tends to increase with increasing die radius and decreasing stiffeners height, the maximum difference is only 6.7% for all tested conditions, which is good for industrial applications. One possible reason for the increasing difference may come from the residual stress present in the machined stiffened plates before CAF, as overestimate of springback by FE simulation has been reported when residual stress effect is ignored [28]. It has also been shown that the residual stress effect becomes less apparent when plates were loaded with a higher stress [29].…”
Section: Springback Behaviour Of Stiffened Plates After Cafmentioning
confidence: 99%
“…Later, extensive work, including improving the creep-age models, such as accounting the precipitate aspect ratio , considering the precipitate dissolution (Li et al, 2017) were performed. Studies have also been made to apply creep-ageing models to study different materials, such as AA6111 (Wang et al, 2004), AA2025 (Gu and Ngan, 2014), and study different conditions, such as T4, T651 (Lam et al, 2015), etc. An alternative approach based on a -projection method for modelling the creep-ageing behaviour, especially for 2024-T3 Al alloys, were also introduced by Lin et al (2013).…”
Section: Introductionmentioning
confidence: 99%